2014
DOI: 10.1111/joor.12172
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between self‐reported sleep bruxism and pain in patients with temporomandibular disorders

Abstract: The aim of this study was to evaluate the association between self-reported sleep bruxism and the age, gender, clinical subtypes of temporomandibular disorders (TMD), pain intensity and grade of chronic pain in patients previously diagnosed with TMD. Thousand two-hundred and twenty patients of the Andalusian Health Service were examined using the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) questionnaire. The inclusion and exclusion criteria were those included in the RDC/TMD criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 32 publications
2
32
2
13
Order By: Relevance
“…Functional symptoms: RDC/TMD diagnosed locked joints and discopathy (with or without arthropathy) were not found to be associated with grinding or clenching the teeth during sleep in the study of Blanco Aguilera et al though Huhtela et al did find an association with “TMJ locking.” “TMJ sounds” were not associated with grinding during sleep in the study of Duckro et al…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Functional symptoms: RDC/TMD diagnosed locked joints and discopathy (with or without arthropathy) were not found to be associated with grinding or clenching the teeth during sleep in the study of Blanco Aguilera et al though Huhtela et al did find an association with “TMJ locking.” “TMJ sounds” were not associated with grinding during sleep in the study of Duckro et al…”
Section: Resultsmentioning
confidence: 90%
“…TMJ symptoms: RDC/TMD diagnosed arthropathy with or without discopathy were assessed by Blanco Aguilera et al, and no association was found with self‐reported sleep bruxism.…”
Section: Resultsmentioning
confidence: 99%
“…Parafunctional habits such as bruxism, nail and lip biting were shown as significant risk factors for TMD pain . Studies show that bruxism is more common among TMD patients than in healthy subjects .…”
Section: Discussionmentioning
confidence: 99%
“…1-3 However, data from polysomnographic recordings of muscle behaviors in TMD and control subjects contradicts this association. 4, 5 The inconsistency amongst findings may be due to differences in, and limitations of, study design, data collection and analytical methods.…”
Section: Introductionmentioning
confidence: 99%